Malaysian Sikhs and gender issues - Sarjit S. Gill (Universiti Kebangsaan Malaysia, 2003)
Sikhism advocates gender equality between men and women in all aspects of their social life. The role and status of women has always been the concern of Sikhism, which asserts the equality of humankind. Based on my observation in Malaysia, I found that, in practice, Sikh women’s status is lower than men. Therefore, the ten Guru’s teachings of equality between men and women have never been fully practiced. Why this is so shall be explored in this paper. It could be suggested that this inequality exist because of the influence of the male majority in the Sikh community, which is a minority in the larger Malaysian context. Therefore, the Sikh male’s unwillingness to give up this dominant role and hence, the women continues to suffer prejudices. It is seems that the male-dominant ideology in the Sikh society is not only found in Malaysia, but throughout the diaspora, and even in their homeland in India.